2017
DOI: 10.18438/b8zh3r
|View full text |Cite
|
Sign up to set email alerts
|

Web-Scale Discovery Services Retrieve Relevant Results in Health Sciences Topics Including MEDLINE Content

Abstract: A Review of: Hanneke, R., & O’Brien, K. K. (2016). Comparison of three web-scale discovery services for health sciences research. Journal of the Medical Library Association, 104(2), 109-117. http://dx.doi.org/10.3163/1536-5050.104.2.004 Abstract Objective – To compare the results of health sciences search queries in three web-scale discovery (WSD) services for relevance, duplicate detection, and retrieval of MEDLINE content. Design – Comparative evaluation and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…These claims are corroborated in a review of three web-scale discovery services with equal access to Pubmed index data. It was demonstrated that there was not enough difference between Primo, Summon, and EBSCO Discovery Services to determine the best discovery service (Hanneke and O'Brien 2016, 113-114) (Stovold 2017), suggesting the exclusivity of indexing records causes the "aggregation [of titles] to become fractured" (Krumenaker 2001), negatively affecting access to databases. Ex Libris and EBSCO have provided conformance statements for the National Information Standards Organization Open Discovery Initiative (National Information Standards Organization 2014), in which "the content provider makes available to Discovery Service Providers core metadata and underlying full-text/orginal content for complete offerings" (EBSCO 2019, n.p.).…”
Section: Exclusivity Of Content and The Problem With Statisticsmentioning
confidence: 99%
“…These claims are corroborated in a review of three web-scale discovery services with equal access to Pubmed index data. It was demonstrated that there was not enough difference between Primo, Summon, and EBSCO Discovery Services to determine the best discovery service (Hanneke and O'Brien 2016, 113-114) (Stovold 2017), suggesting the exclusivity of indexing records causes the "aggregation [of titles] to become fractured" (Krumenaker 2001), negatively affecting access to databases. Ex Libris and EBSCO have provided conformance statements for the National Information Standards Organization Open Discovery Initiative (National Information Standards Organization 2014), in which "the content provider makes available to Discovery Service Providers core metadata and underlying full-text/orginal content for complete offerings" (EBSCO 2019, n.p.).…”
Section: Exclusivity Of Content and The Problem With Statisticsmentioning
confidence: 99%